Amyloid aggregation in temporal regions is associated with longitudinal memory decline in cognitively unimpaired Apoe‐ε4 carriers. (31st December 2021) - Brugulat‐Serrat, Anna; Sánchez‐Benavides, Gonzalo; Cacciaglia, Raffaele; Salvadó, Gemma; Collij, Lyduine E.; Buckley, Christopher; Van Berckel, Bary N.M.; Perissinotti, Andrés; Niñerola‐Baizán, Aida; Milà‐Alomà, Marta; Operto, Grégory; Falcon, Carles; et al.
Abstract: Background: Evidence shows that APOE‐ε4 is associated with amyloid‐beta (Aβ) aggregation in the medial temporal lobe (MTL), a crucial region supporting episodic memory (EM), early in the AD continuum . However, the impact of Aβ aggregation in the MTL of cognitively unimpaired (CU) APOE‐ε4 carriers has not been explored. We determine whether abnormal Aβ in the MTL of CU individuals APOE‐ε4 carriers has an impact on EM change. Method: The study included 352 CU ALFA+ study individuals (age 45‐70) who completed a baseline cognitive assessment with valid T1w MRI, [ 18 F]‐flutemetamol Aβ PET, CSF, and APOE genotyping, and also had a second cognitive assessment after 3 years. [ 18 F]‐flutemetamol scans were visually assessed globally to rate the scan as positive or negative and regionally. CSF p‐tau, Aβ‐40 and Aβ‐42 concentrations were determined using the exploratory Roche NeuroToolKit assays, a panel of automated robust prototype immunoassays, and Elecsys® immunoassays (both Roche Diagnostics International Ltd). Hippocampal volumes (HV) were obtained from the T1w MRIs with Freesurfer 6.0. EM was assessed by the Memory and Binding Tests subscore Total Paired Recall (TPR). Annualized memory change was the dependent variable in linear models using regional or global visual read (VR), CSF biomarkers and HV as predictors, and age, sex, education and APOE‐ε4 as covariates. Interaction terms with APOE‐ε4 *VR were also modeled. Result: 57 (16.2%) participants were global VR amyloid‐positive and 41 (71.9%) were APOE‐ε4 carriers. For annualized change in memory, we found that APOE‐ε4 carriership modified the association between temporal VR and annualized change ( p =0.02) (Figure 1). 29 (5.4%) were amyloid‐positive in temporal VR, of them 19 (65.5%) APOE‐ε4 carriers. This interaction remained significant after adjusting by CSF Aβ42/Aβ40 and ptau/Aβ42 ratios, and HV (Table 1). No significant interaction was found with global VR. Conclusion: APOE‐ε4 carriers with a positive temporal VR exhibited a decline in EM. This result shows the effects on cognition of previous findings showing the association between APOE‐ε4 and Aβ aggregation in the MTL for any given level of soluble Aβ alterations. Moreover, this work supports that regional VRs can detect early Aβ pathology with relevant effects on cognition.